2015
DOI: 10.1186/s12977-015-0142-z
|View full text |Cite
|
Sign up to set email alerts
|

Elevated expression of LAG-3, but not PD-1, is associated with impaired iNKT cytokine production during chronic HIV-1 infection and treatment

Abstract: BackgroundLAG-3 is a potent negative regulator of the immune response but its impact in HIV infection in poorly understood. Unlike exhaustion markers such as PD-1, Tim-3, 2B4 and CD160, LAG-3 is poorly expressed on bulk and antigen-specific T cells during chronic HIV infection and its expression on innate lymphocyte subsets is not well understood. The aim of this study was to assess LAG-3 expression and association with cellular dysfunction on T cells, NK cells and iNKT cells among a cohort of healthy and HIV-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
37
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(37 citation statements)
references
References 80 publications
0
37
0
Order By: Relevance
“…66 Moreover, elevated expression of LAG3 was associated with impaired iNKT cytokine production (IFNγ) during chronic HIV infection, but this was not noted on other T-cell subsets. 67 Interestingly, PD1 expression levels were not affected. The functional significance of LAG3 on iNKT cells in this scenario is unclear, although a significant percentage (~40%) of this cell type expressed LAG3 in this cohort, which inversely correlated with IFNγ production.…”
Section: Physiological Role Of Lag3mentioning
confidence: 95%
See 1 more Smart Citation
“…66 Moreover, elevated expression of LAG3 was associated with impaired iNKT cytokine production (IFNγ) during chronic HIV infection, but this was not noted on other T-cell subsets. 67 Interestingly, PD1 expression levels were not affected. The functional significance of LAG3 on iNKT cells in this scenario is unclear, although a significant percentage (~40%) of this cell type expressed LAG3 in this cohort, which inversely correlated with IFNγ production.…”
Section: Physiological Role Of Lag3mentioning
confidence: 95%
“…Proliferation of activated NKT cells is reduced as a result of LAG3 signaling, resulting in cell cycle arrest in the S phase . Moreover, elevated expression of LAG3 was associated with impaired iNKT cytokine production (IFNγ) during chronic HIV infection, but this was not noted on other T‐cell subsets . Interestingly, PD1 expression levels were not affected.…”
Section: Physiological Role Of Lag3mentioning
confidence: 99%
“…In tuberculosis, sLAG‐3 is elevated both in healthy people who have been exposed to the bacteria and in tuberculosis patients with good prognoses, indicating that sLAG‐3 could modulate an anti‐bacterial immune response in mycobacterium tuberculosis . In acquired immune deficiency, high expression of LAG‐3 was correlated with impaired invariant natural killer T cell cytokine production for the duration of chronic human immunodeficiency virus (HIV)‐1 infection and treatment . Targeting the LAG‐3 pathway has an immune regulatory effect and can enhance immune reconstitution in HIV‐infected patients …”
Section: Lymphocyte‐activation Gene‐3 In Diseasementioning
confidence: 99%
“…(52) In acquired immune deficiency, high expression of LAG-3 was correlated with impaired invariant natural killer T cell cytokine production for the duration of chronic human immunodeficiency virus (HIV)-1 infection and treatment. (53,54) Targeting the LAG-3 pathway has an immune regulatory effect and can enhance immune reconstitution in HIV-infected patients. (55) Lymphocyte-activation gene-3 in cancer LAG-3 expression was also observed in various cancer types.…”
Section: Lymphocyte-activation Gene-3 In Diseasementioning
confidence: 99%
“…As a result of LAG3 signaling, proliferation of activated NKT cells was reduced, resulting in cell cycle arrest in the phase S (62). Moreover, researchers also found that overexpression of LAG3 was associated with impaired iNKT cytokine production (IFNγ) during chronic HIV infection, nevertheless this was not discovered on other T-cell subsets (63). As for monocytic lineage, one previous study had suggested that a soluble monomeric form of LAG3 (sLAG3), generated by alternative splicing, impaired the differentiation of monocytes into DCs and macrophages, which subsequently had diminished its immunostimulatory capacity (64).…”
Section: Discussionmentioning
confidence: 99%